Analisis Permintaan Transportasi Laut Berdasarkan Data Historis Keberangkatan Penumpang di Jayapura - Prawardani, Dinda Sekar Selni; Pabinte, Marcelia Eliezer (Universitas Muhammadiyah Palembang, 2025)
Indonesia, an archipelago of over 17,000 islands, relies heavily on maritime transportation for inter-regional connectivity, given that its waters constitute over 62% of its total area. Situated on a strategic global trade route, Indonesia is developing its maritime infrastructure through initiatives like the